Stiff PBST and polylactic acid composite fiber, preparation method, use and surgical clothing thereof
Through the preparation of broad-leaved PBST and polylactic acid composite fibers, the combination of PBST fiber and polylactic acid fibers is used to solve the problems of high cost of polylactic fibers and limited application of PBST, and low-cost, biodegradable composite fibers are realized. Suitable for disposable surgical clothing, with excellent broadness and environmental protection.
Patent Information
- Application Number
- CN202111395933.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-23
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-11-23
AI Technical Summary
The high cost of polylactic fiber limits its wide application in medical gowns, medical surgical gowns and other fields. The application of existing PBST is limited and costs need to be reduced to expand the scope of application.
The preparation method includes esterification reaction, pre-polycondensation, final polycondensation and slicing treatment to form excellent esterification and Biodegradable composite fibers.
The PBST and polylactic acid composite fibers have a tensile strength of 3.5CN/dtex-4.5CN/dtex and an elongation of break of 25%-35%. They are suitable for disposable surgical clothing, completely biodegradable, and do not Generate garbage and friendly environment.
Smart Images

Figure BDA0003369926320000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite fibers, in particular to a stiff PBST and polylactic acid composite fiber, and a preparation method and application thereof. Background Art
[0002] At present, the material used as clothing including underwear, outerwear and other fields includes polylactic acid, which is pollution-free in the production process, and the product can be biodegraded, and the cycle in nature is realized, so it is an ideal green polymer material, low cost, has been realized large-scale production, and is widely used in the preparation of biodegradable fibers, films, and plastic products, and has a wide range of uses, and can be used as packaging materials, fibers and nonwovens, etc. However, the cost of polylactic acid fiber is high, which often limits its application in wider occasions, such as medical gowns, medical surgical gowns, etc., and it is necessary to reduce costs. Poly (butylene succinate-co-terephthalate), PBST, as a good biodegradable material, has a lower price, but the prior art is more limited for the application of PBST. Summary of the invention
[0003] In view of this, the present invention provides a stiff PBST and polylactic acid composite fiber, a manufacturing method, use and surgical clothing thereof, which can be more suitable for practical use.
[0004] In order to achieve the above first purpose, the technical solution of the stiff PBST and polylactic acid composite fiber provided by the present invention is as follows:
[0005] The stiff PBST and polylactic acid composite fiber provided by the present invention comprises PBST fiber and polylactic acid fiber. After the composite fiber is formed, the PBST fiber is the sheath of the composite fiber, and the polylactic acid fiber is the core layer of the composite fiber.
[0006] The stiff PBST and polylactic acid composite fiber provided by the present invention can be further realized by adopting the following technical measures.
[0007] Preferably, the ratio of the cross-sectional area of the core layer to the cross-sectional area of the skin layer is in the range of (20-50): (50-80).
[0008] Preferably, when observing from the cross section of the composite fiber, the core layer and the skin layer are of a concentric structure.
[0009] Preferably, the tensile strength of the composite fiber is in the range of 3.5CN / dtex-4.5CN / dtex, and the elongation at break of the composite fiber is in the range of 25%-35%.
[0010] In order to achieve the above second purpose, the technical scheme of the preparation method of the stiff PBST composite fiber provided by the present invention is as follows:
[0011] The preparation method of the stiff PBST and polylactic acid composite fiber provided by the present invention comprises the following steps:
[0012] Respectively obtaining the PBST slice and the polylactic acid slice;
[0013] The PBST slices and the polylactic acid slices are subjected to composite spinning, so that the stiff PBST fibers are located in the cortex of the composite fibers, and the polylactic acid fibers form the core layer of the composite fibers, thereby obtaining the PBST and polylactic acid composite fibers.
[0014] The method for preparing the stiff PBST and polylactic acid composite fiber provided by the present invention can also be further implemented by adopting the following technical measures.
[0015] Preferably, the method for obtaining PBST slices comprises the following steps:
[0016] After mixing terephthalic acid, succinic acid, butanediol and a catalyst, the mixture is added into a polymerization reactor, and a first esterification reaction is carried out at 160° C.-180° C. The first esterification reaction is terminated when the esterification rate reaches 49.2%-49.9%. The molar ratio of terephthalic acid, succinic acid and butanediol is in the range of 1.00:(1.30-1.34):(2.7-2.90), and the amount of the catalyst added is 0.02%-0.03% of the molar amount of the sum of the succinic acid and terephthalic acid;
[0017] The temperature is raised to 205°C-215°C, and the second esterification reaction is completed when the esterification rate reaches 98.8%-99.8%;
[0018] The temperature is raised to 240° C., a matting agent is added from the feeding port of the polymerization reactor, stirred for 15-20 minutes, and a pre-polycondensation reaction is carried out for 20 minutes to 40 minutes, wherein the amount of the matting agent added is 0.5% to 1.5% of the sum of the weight of terephthalic acid and succinic acid in terms of weight percentage;
[0019] The process is vacuumized, and the temperature is raised to 250° C.-260° C. to carry out a final polycondensation reaction. When the intrinsic viscosity is 0.75 dL / g-0.77 dL / g, the material is discharged, dried, and pelletized to obtain the stiff PBST slices. The operating environment of the drying step is as follows: the temperature ranges from 100° C. to 105° C., and the drying duration ranges from 18 h to 24 h.
[0020] Preferably, during the steps of evacuating the vacuum, heating to 250° C.-260° C., performing the final polycondensation reaction, and discharging, drying, and pelletizing to obtain the PBST slices, when the intrinsic viscosity is 0.75 dL / g-0.77 dL / g, the method for determining the intrinsic viscosity comprises the following steps:
[0021] Phenol and tetrachloroethane in a mass ratio of 1:1 are prepared as a solvent;
[0022] Adding the PBST into the solvent to prepare a solution with a content of 0.1 g / dL;
[0023] The intrinsic viscosity is obtained by measuring the intrinsic viscosity of the solution at 25°C using an Ubbelohde viscometer.
[0024] Preferably, in the step of mixing terephthalic acid, succinic acid, butanediol and a catalyst, adding the mixture into a polymerization reactor, and carrying out a first esterification reaction at 160° C.-180° C., the first esterification reaction is terminated when the esterification rate reaches 49.2%-49.9%, and the catalyst is tetraisopropyl titanate.
[0025] Preferably, the method for obtaining the polylactic acid slice comprises the following steps:
[0026] Put polylactic acid into a mixer, add a matting agent, the amount of the matting agent added is 0.5%-1.5% of the mass of the polylactic acid, stir for 3min-5min to obtain a mixed material;
[0027] The mixed material is placed at the main feeding port of a twin-screw extruder with a length-to-diameter ratio of (42:1)-(60:1), melt-extruded and granulated, and the extruded material is cooled, air-dried, pelletized and dried in sequence to obtain the polylactic acid slices; wherein the drying is vacuum drying, the drying temperature ranges from 105°C to 115°C, and the drying duration ranges from 24h to 36h.
[0028] Preferably, the mixed material is placed in the main feeding port of a twin-screw extruder with a length-to-diameter ratio of (42:1)-(60:1), melt-extruded and granulated, and the extruded material is cooled, air-dried, pelletized and dried in sequence to obtain the polylactic acid slices. In the process, the temperature setting range of the twin-screw extruder is 165°C-210°C, the screw speed is 350rpm-400rpm, and the temperature of each zone of the twin-screw extruder is: zone one temperature: 165°C-180°C, zone two temperature: 180°C-190°C, zone three temperature: 190°C-200°C, zone four temperature: 200°C-210°C, zone five temperature: 200°C-210°C, zone six temperature: 195°C-200°C, zone seven temperature: 190°C-195°C.
[0029] Preferably, the matting agent is titanium dioxide with a purity ranging from 99.0% to 99.9%, a rutile type, a particle size of 50nm to 100nm, white particles, and a weight average molecular weight of 70,000 to 80,000.
[0030] Preferably, the composite spinning process of the PBST slice and the polylactic acid slice is achieved by a one-step spinning-stretching method, and the stretching multiple ranges from 4 to 6 times;
[0031] The process conditions for composite spinning of the polylactic acid slice core layer and the PBST slice skin layer include:
[0032] For the cortex:
[0033] The temperature range of the components is 170℃-190℃.
[0034] The screw pressure ranges from 10MPa to 12MPa;
[0035] For the core layer:
[0036] The temperature range of the components is 200℃-220℃.
[0037] The screw pressure range is 8.0MPa-10.0MPa.
[0038] The spinning speed ranges from 1200m / min to 1500m / min;
[0039] The cooling method is air cooling, the blowing method adopts side blowing, and the blowing rate ranges from 3m / min to 5m / min.
[0040] In order to achieve the third purpose, the technical scheme of the use of the stiff PBST and polylactic acid composite fiber provided by the present invention is as follows:
[0041] The stiff PBST and polylactic acid composite fiber provided by the invention is used for disposable surgical gowns.
[0042] In order to achieve the fourth objective, the technical solution of the surgical garment provided by the present invention is as follows:
[0043] The surgical garment provided by the present invention is made of the stiff PBST and polylactic acid composite fiber provided by the present invention.
[0044] The tensile strength of the stiff PBST and polylactic acid composite fiber prepared by the preparation method provided by the present invention reaches a value range of 3.5CN / dtex-4.5CN / dtex, the breaking elongation of the prepared stiff PBST and polylactic acid copolymer composite fiber reaches a value range of 25%-35%, and the initial modulus reaches 45-55CN.dtex-1. Compared with pure PBST fiber, the stiff PBST and polylactic acid composite fiber provided by the present invention has better stiffness; compared with pure polylactic acid fiber, the stiff PBST and polylactic acid composite fiber provided by the present invention can be better suitable for disposable surgical clothing, can be completely biodegradable, and will not generate garbage after being discarded, and will not have any impact on the environment. DETAILED DESCRIPTION
[0045] In view of this, the present invention provides a stiff PBST and polylactic acid composite fiber, a manufacturing method, use and surgical clothing thereof, which is completely biodegradable and will not generate garbage or have any impact on the environment after being discarded, thus being more suitable for practical use.
[0046] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a stiff PBST and polylactic acid composite fiber, its manufacturing method, use and surgical clothing proposed by the present invention, its specific implementation method, structure, characteristics and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable form.
[0047] The term "and / or" in this article is merely a description of the association relationship between associated objects, indicating that three relationships may exist, for example, A and / or B. Specifically, it is understood that: A and B may be included at the same time, A may exist alone, or B may exist alone, and any of the above three situations may be met.
[0048] Example 1
[0049] Preparation of polylactic acid slices:
[0050] Weigh the polylactic acid, put it into a high-speed mixer, add a matting agent in an amount of 0.5% of the mass of the polylactic acid, stir at a low speed for 3 minutes, take it out and set aside.
[0051] The mixed materials are placed in the main feeding port of a twin-screw extruder with a length-to-diameter ratio of 42:1, melt-extruded and granulated, and the extruded materials are cooled, air-dried, pelletized and dried to obtain semi-dull polylactic acid.
[0052] The matting agent is titanium dioxide, purity 99.9%, rutile type, particle size 50nm. Polylactic acid, white particles, weight average molecular weight 70000.
[0053] The temperature setting values of the twin-screw extruder are as follows: zone 1 temperature: 165°C, zone 2 temperature: 180°C, zone 3 temperature: 190°C, zone 4 temperature: 200°C, zone 5 temperature: 200°C, zone 6 temperature: 195°C, zone 7 temperature: 190°C, and the screw speed is 350rpm.
[0054] The semi-dull polylactic acid is vacuum dried to obtain dried semi-dull polylactic acid slices, wherein the vacuum drying temperature is 105° C. and the vacuum drying duration is 24 hours.
[0055] Preparation of PBST slices: After terephthalic acid, succinic acid, butanediol and a catalyst are mixed, they are added into a polymerization reactor, and the first esterification reaction is carried out at 160°C. When the esterification rate reaches 49.2%, the first esterification reaction ends; the temperature is raised to 205°C for the second esterification reaction. When the esterification rate reaches 98.8%, the second esterification reaction ends, wherein the molar ratio of terephthalic acid to succinic acid to butanediol is 1.00:1.30:2.70. The molar amount of the catalyst tetraisopropyl titanate is 0.025% of the molar amount of the sum of succinic acid and terephthalic acid.
[0056] The temperature was raised to 240°C, and a matting agent of 0.5% by weight of the sum of terephthalic acid and succinic acid was added from the feeding port of the polymerization reactor. The matting agent was titanium dioxide with a purity of 99.9%, a rutile type, and a particle size of 50nm. The stirring was started and stirred for 15 minutes, and a pre-polycondensation reaction was carried out for 20 minutes; then the vacuum was slowly drawn and the temperature was raised to 250°C for a final polycondensation reaction. When the intrinsic viscosity was 0.75dL / g, the material was discharged and pelletized to obtain a semi-matt PBST copolymer. After drying, PBST slices were obtained. The drying temperature was 105°C and the drying duration was 18 hours.
[0057] The spinning process of the stiff PBST and polylactic acid composite fiber is achieved by a one-step spinning-stretching method, with a stretching multiple of 4 times; the ratio of the cross-sectional area of the core layer to the cross-sectional area of the skin layer is 30:70.
[0058] The process conditions for composite spinning of the polylactic acid slice core layer and the PBST slice skin layer include: for the skin layer: zone one temperature: 170°C; zone two temperature: 180°C; zone three temperature: 190°C, and the screw pressure is 10MPa; for the core layer: zone one temperature: 200°C; zone two temperature: 210°C; zone three temperature: 220°C, the screw pressure is 8.0MPa, and the spinning speed is 1200m / min; the cooling method is air cooling, and the blowing method adopts side blowing, with a blowing rate of 5m / min; the spinning specification is 50D / 24f.
[0059] Example 2
[0060] Preparation of polylactic acid slices:
[0061] Weigh the polylactic acid, put it into a high-speed mixer, add a matting agent in an amount of 0.5% of the mass of the polylactic acid, stir at a low speed for 3 minutes, take it out and set aside.
[0062] The mixed materials are placed in the main feeding port of a twin-screw extruder with a length-to-diameter ratio of 42:1, melt-extruded and granulated, and the extruded materials are cooled, air-dried, pelletized and dried to obtain semi-dull polylactic acid.
[0063] The matting agent is titanium dioxide, purity 99.9%, rutile type, particle size 50nm. Polylactic acid, white particles, weight average molecular weight 70000.
[0064] The temperature setting values of the twin-screw extruder are as follows: zone 1 temperature: 165°C, zone 2 temperature: 180°C, zone 3 temperature: 190°C, zone 4 temperature: 200°C, zone 5 temperature: 200°C, zone 6 temperature: 195°C, zone 7 temperature: 190°C, and the screw speed is 350rpm.
[0065] The semi-dull polylactic acid is vacuum dried to obtain dried semi-dull polylactic acid slices, wherein the vacuum drying temperature is 105° C. and the vacuum drying duration is 24 hours.
[0066] Preparation of PBST slices: After terephthalic acid, succinic acid, butanediol and a catalyst are mixed, they are added to a polymerization reactor, and the first esterification reaction is carried out at 160°C. When the esterification rate reaches 49.2%, the first esterification reaction ends; the temperature is raised to 205°C for the second esterification reaction. When the esterification rate reaches 98.8%, the second esterification reaction ends, wherein the molar ratio of terephthalic acid to succinic acid to butanediol is 1.00:1.31:2.74. The molar amount of the catalyst tetraisopropyl titanate is 0.025% of the molar amount of the sum of succinic acid and terephthalic acid.
[0067] The temperature was raised to 240°C, and a matting agent of 0.5% by weight of the sum of terephthalic acid and succinic acid was added from the feeding port of the polymerization reactor. The matting agent was titanium dioxide with a purity of 99.9%, a rutile type, and a particle size of 50nm. The stirring was started and stirred for 15 minutes, and a pre-polycondensation reaction was carried out for 20 minutes; then the vacuum was slowly drawn and the temperature was raised to 250°C for a final polycondensation reaction. When the intrinsic viscosity was 0.75dL / g, the material was discharged and pelletized to obtain a semi-matt PBST copolymer. After drying, PBST slices were obtained. The drying temperature was 105°C and the drying duration was 18 hours.
[0068] The spinning process of the stiff PBST and polylactic acid composite fiber is achieved by a one-step spinning-stretching method, with a stretching multiple of 4 times; the ratio of the cross-sectional area of the core layer to the cross-sectional area of the skin layer is 30:70.
[0069] The process conditions for composite spinning of the polylactic acid slice core layer and the PBST slice skin layer include: for the skin layer: zone one temperature: 170°C; zone two temperature: 180°C; zone three temperature: 190°C, and the screw pressure is 10MPa; for the core layer: zone one temperature: 200°C; zone two temperature: 210°C; zone three temperature: 220°C, the screw pressure is 8.0MPa, and the spinning speed is 1200m / min; the cooling method is air cooling, and the blowing method adopts side blowing, with a blowing rate of 5m / min; the spinning specification is 50D / 24f.
[0070] Example 3
[0071] Preparation of polylactic acid slices:
[0072] Weigh the polylactic acid, put it into a high-speed mixer, add a matting agent in an amount of 0.5% of the mass of the polylactic acid, stir at a low speed for 3 minutes, take it out and set aside.
[0073] The mixed materials are placed in the main feeding port of a twin-screw extruder with a length-to-diameter ratio of 42:1, melt-extruded and granulated, and the extruded materials are cooled, air-dried, pelletized and dried to obtain semi-dull polylactic acid.
[0074] The matting agent is titanium dioxide, purity 99.9%, type rutile, particle size 50nm. Polylactic acid, white particles, weight average molecular weight 70000.
[0075] The temperature setting values of the twin-screw extruder are as follows: zone 1 temperature: 165°C, zone 2 temperature: 180°C, zone 3 temperature: 190°C, zone 4 temperature: 200°C, zone 5 temperature: 200°C, zone 6 temperature: 195°C, zone 7 temperature: 190°C, and the screw speed is 350rpm.
[0076] The semi-dull polylactic acid is vacuum dried to obtain dried semi-dull polylactic acid slices, wherein the vacuum drying temperature is 105° C. and the vacuum drying duration is 24 hours.
[0077] Preparation of PBST slices: After terephthalic acid, succinic acid, butanediol and a catalyst are mixed, they are added into a polymerization reactor, and the first esterification reaction is carried out at 160°C. When the esterification rate reaches 49.2%, the first esterification reaction ends; the temperature is raised to 205°C for the second esterification reaction. When the esterification rate reaches 98.8%, the second esterification reaction ends, wherein the molar ratio of terephthalic acid to succinic acid to butanediol is 1.00:1.32:2.80. The molar amount of the catalyst tetraisopropyl titanate is 0.025% of the molar amount of the sum of succinic acid and terephthalic acid.
[0078] The temperature was raised to 240°C, and a matting agent of 0.5% by weight of the sum of terephthalic acid and succinic acid was added from the feeding port of the polymerization reactor. The matting agent was titanium dioxide with a purity of 99.9%, a rutile type, and a particle size of 50nm. The stirring was started and stirred for 15 minutes, and a pre-polycondensation reaction was carried out for 20 minutes; then the vacuum was slowly drawn and the temperature was raised to 250°C for a final polycondensation reaction. When the intrinsic viscosity was 0.75dL / g, the material was discharged and pelletized to obtain a semi-matt PBST copolymer. After drying, PBST slices were obtained. The drying temperature was 105°C and the drying duration was 18 hours.
[0079] The spinning process of the stiff PBST and polylactic acid composite fiber is achieved by a one-step spinning-stretching method, with a stretching multiple of 4 times; the ratio of the cross-sectional area of the core layer to the cross-sectional area of the skin layer is 30:70.
[0080] The process conditions for composite spinning of the polylactic acid slice core layer and the PBST slice skin layer include: for the skin layer: zone one temperature: 170°C; zone two temperature: 180°C; zone three temperature: 190°C, and the screw pressure is 10MPa; for the core layer: zone one temperature: 200°C; zone two temperature: 210°C; zone three temperature: 220°C, the screw pressure is 8.0MPa, and the spinning speed is 1200m / min; the cooling method is air cooling, and the blowing method adopts side blowing, with a blowing rate of 5m / min; the spinning specification is 50D / 24f.
[0081] Example 4
[0082] Preparation of polylactic acid slices:
[0083] Weigh the polylactic acid, put it into a high-speed mixer, add a matting agent in an amount of 0.5% of the mass of the polylactic acid, stir at a low speed for 3 minutes, take it out and set aside.
[0084] The mixed materials are placed in the main feeding port of a twin-screw extruder with a length-to-diameter ratio of 42:1, melt-extruded and granulated, and the extruded materials are cooled, air-dried, pelletized and dried to obtain semi-dull polylactic acid.
[0085] The matting agent is titanium dioxide, purity 99.9%, rutile type, particle size 50nm. Polylactic acid, white particles, weight average molecular weight 70000.
[0086] The temperature setting values of the twin-screw extruder are as follows: zone 1 temperature: 165°C, zone 2 temperature: 180°C, zone 3 temperature: 190°C, zone 4 temperature: 200°C, zone 5 temperature: 200°C, zone 6 temperature: 195°C, zone 7 temperature: 190°C, and the screw speed is 350rpm.
[0087] The semi-dull polylactic acid is vacuum dried to obtain dried semi-dull polylactic acid slices, wherein the vacuum drying temperature is 105° C. and the vacuum drying duration is 24 hours.
[0088] Preparation of PBST slices: After terephthalic acid, succinic acid, butanediol and a catalyst are mixed, they are added into a polymerization reactor, and the first esterification reaction is carried out at 160°C. When the esterification rate reaches 49.2%, the first esterification reaction ends; the temperature is raised to 205°C for the second esterification reaction. When the esterification rate reaches 98.8%, the second esterification reaction ends, wherein the molar ratio of terephthalic acid to succinic acid to butanediol is 1.00:1.34:2.90. The molar amount of the catalyst tetraisopropyl titanate is 0.025% of the molar amount of the sum of succinic acid and terephthalic acid.
[0089] The temperature was raised to 240°C, and a matting agent of 0.5% by weight of the sum of terephthalic acid and succinic acid was added from the feeding port of the polymerization reactor. The matting agent was titanium dioxide with a purity of 99.9%, a rutile type, and a particle size of 50nm. The stirring was started and stirred for 15 minutes, and a pre-polycondensation reaction was carried out for 20 minutes; then the vacuum was slowly drawn and the temperature was raised to 250°C for a final polycondensation reaction. When the intrinsic viscosity was 0.75dL / g, the material was discharged and pelletized to obtain a semi-matt PBST copolymer. After drying, PBST slices were obtained. The drying temperature was 105°C and the drying duration was 18 hours.
[0090] The spinning process of the stiff PBST and polylactic acid composite fiber is achieved by a one-step spinning-stretching method, with a stretching multiple of 4 times; the ratio of the cross-sectional area of the core layer to the cross-sectional area of the skin layer is 30:70.
[0091] The process conditions for composite spinning of the polylactic acid slice core layer and the PBST slice skin layer include: for the skin layer: zone one temperature: 170°C; zone two temperature: 180°C; zone three temperature: 190°C, and the screw pressure is 10MPa; for the core layer: zone one temperature: 200°C; zone two temperature: 210°C; zone three temperature: 220°C, the screw pressure is 8.0MPa, and the spinning speed is 1200m / min; the cooling method is air cooling, and the blowing method adopts side blowing, with a blowing rate of 5m / min; the spinning specification is 50D / 24f.
[0092] Example 5
[0093] Preparation of polylactic acid slices:
[0094] Weigh the polylactic acid, put it into a high-speed mixer, add a matting agent in an amount of 0.5% of the mass of the polylactic acid, stir at a low speed for 3 minutes, take it out and set aside.
[0095] The mixed materials are placed at the main feeding port of a twin-screw extruder with a length-to-diameter ratio of 42:1, and melt-extruded into granules. The extruded materials are cooled, air-dried, pelletized, and dried to obtain polylactic acid chips.
[0096] The matting agent is titanium dioxide, purity 99.9%, type rutile, particle size 50nm, polylactic acid, white particles, weight average molecular weight 70000.
[0097] The temperature setting range of the twin-screw extruder is: zone 1 temperature: 165°C, zone 2 temperature: 180°C, zone 3 temperature: 190°C, zone 4 temperature: 200°C, zone 5 temperature: 200°C, zone 6 temperature: 195°C, zone 7 temperature: 190°C, and the screw speed is 350rpm.
[0098] The semi-dull polylactic acid is vacuum dried to obtain dried semi-dull polylactic acid slices, wherein the vacuum drying temperature is 105° C. and the duration of the vacuum drying is 24 hours to obtain the polylactic acid slices.
[0099] Preparation of PBST sections:
[0100] After mixing terephthalic acid, succinic acid, butanediol and a catalyst, the mixture is added into a polymerization reactor, and an esterification reaction is carried out at 180°C. When the esterification rate reaches 49.2%, the first esterification reaction is completed; the temperature is raised to 205°C for a second esterification reaction. When the esterification rate reaches 98.8%, the second esterification reaction is completed, wherein the molar ratio of terephthalic acid to succinic acid is 1:1.33, and the molar ratio of terephthalic acid to succinic acid and to butanediol is 1:3. The molar amount of the catalyst tetraisopropyl titanate is 0.025% of the molar amount of the sum of succinic acid and terephthalic acid.
[0101] The temperature was raised to 240°C, and a matting agent of 1.5% of the weight percentage of the sum of the weight of terephthalic acid and succinic acid was added from the feeding port of the polymerization kettle. The matting agent was titanium dioxide with a purity of 99.9%, a rutile type, and a particle size of 50nm. Stirring was started for 15 minutes, and a pre-polycondensation reaction was carried out for 20 minutes; then vacuum was slowly drawn, and the temperature was raised to 250°C for a polycondensation reaction. When the intrinsic viscosity was 0.75dL / g, the material was discharged, and semi-matt PBST copolymer was obtained after pelletizing. After drying, PBST slices were obtained. The drying temperature was 105°C and the drying duration was 18h.
[0102] The spinning process of the stiff PBST and polylactic acid composite fiber is achieved by a one-step spinning-stretching method, with a stretching multiple of 4 times; the ratio of the cross-sectional area of the core layer to the cross-sectional area of the skin layer is 35:65.
[0103] The process conditions for composite spinning of the polylactic acid slice core layer and the PBST slice skin layer include: for the skin layer: zone one temperature: 170°C; zone two temperature: 180°C; zone three temperature: 190°C, and the screw pressure is 10MPa; for the core layer: zone one temperature: 200°C; zone two temperature: 210°C; zone three temperature: 220°C, the screw pressure is 8.0MPaMPa, and the spinning speed is 1200m / min; the cooling method is air cooling, and the blowing method adopts side blowing, with a blowing rate of 5m / min; the spinning specification is 50D / 24f.
[0104] Comparative Example 1
[0105] Preparation of PBST sections:
[0106] After mixing terephthalic acid, succinic acid, butanediol and a catalyst, the mixture is added into a polymerization reactor, and the first esterification reaction is carried out at 160°C. When the esterification rate reaches 49.2%, the first esterification reaction is completed; the temperature is further raised to 205°C for the second esterification reaction. When the esterification rate reaches 98.8%, the second esterification reaction is completed, wherein the molar ratio of terephthalic acid to succinic acid to butanediol is 1.00:1.30:2.70. The molar amount of the catalyst tetraisopropyl titanate is 0.025% of the molar amount of the sum of succinic acid and terephthalic acid.
[0107] The temperature was raised to 240°C, and a matting agent of 0.5% of the weight percentage of the total weight of terephthalic acid and succinic acid was added from the feeding port of the polymerization reactor. The matting agent was titanium dioxide with a purity of 99.9%, a rutile type, and a particle size of 50nm. Stirring was started for 15 minutes, and a pre-polycondensation reaction was carried out for 20 minutes; then vacuum was slowly drawn, and the temperature was raised to 250°C for a final polycondensation reaction. When the intrinsic viscosity was 0.75dL / g, the material was discharged, and semi-matt PBST copolymer was obtained after pelletizing. After drying, PBST slices were obtained. The drying temperature was 105°C and the drying duration was 18 hours.
[0108] The spinning process of PBST fiber is achieved by a one-step spinning-stretching method, with a stretching ratio of 4 times; the spinning process conditions include: zone one temperature: 170°C; zone two temperature: 180°C; zone three temperature: 190°C, the spinning screw pressure is 10MPa, and the spinning speed is 1200m / min; the cooling method is air cooling, and the blowing method is side blowing, with a blowing rate of 5m / min; the spinning specification is 50D / 24f.
[0109] Comparative Example 2
[0110] Preparation of PBST sections:
[0111] After mixing terephthalic acid, succinic acid, butanediol and a catalyst, the mixture is added into a polymerization reactor, and the first esterification reaction is carried out at 180°C. When the esterification rate reaches 49.2%, the first esterification reaction is completed; the temperature is further raised to 205°C for the second esterification reaction. When the esterification rate reaches 98.8%, the second esterification reaction is completed, wherein the molar ratio of terephthalic acid to succinic acid to butanediol is 1.00:1.31:2.74. The molar amount of the catalyst tetraisopropyl titanate is 0.025% of the molar amount of the sum of succinic acid and terephthalic acid.
[0112] The temperature was raised to 240°C, and a matting agent of 1.5% of the weight percentage of the total weight of terephthalic acid and succinic acid was added from the feeding port of the polymerization kettle. The matting agent was titanium dioxide with a purity of 99.9%, a rutile type, and a particle size of 50nm. Stirring was started for 15 minutes, and a pre-polycondensation reaction was carried out for 20 minutes; then vacuum was slowly drawn, and the temperature was raised to 250°C for a polycondensation reaction. When the intrinsic viscosity was 0.75dL / g, the material was discharged, and semi-matt PBST copolymer was obtained after pelletizing. After drying, PBST slices were obtained. The drying temperature was 105°C and the drying duration was 18 hours.
[0113] The spinning process of PBST fiber is achieved by a one-step spinning-stretching method with a stretching ratio of 4 times; the spinning process conditions include: zone 1 temperature: 170°C; zone 2 temperature: 180°C; zone 3 temperature: 190°C, screw pressure of 10MPa, spinning speed of 1200m / min; air cooling, side blowing, and blowing rate of 5m / min; spinning specification is 50D / 24f.
[0114] The above embodiments and comparative examples were subjected to performance tests, wherein the test standards for tensile strength, elongation at break and initial modulus were: ISO11566-1996, and the test standard for degradation rate was: ISO14855-1:2005. The performance test results are detailed in Table 1:
[0115] Table 1 Performance index of composite fiber
[0116]
[0117] From Table 1 above, it can be seen that the tensile strength of the stiff PBST and polylactic acid composite fiber prepared by the preparation method provided in the embodiment of the present invention reaches a value range of 3.5CN / dtex-4.5CN / dtex, the elongation at break of the prepared stiff PBST and polylactic acid copolymer composite fiber ranges from 25% to 35%, and the initial modulus reaches 45-55CN.dtex-1. Compared with pure PBST fiber, the initial modulus values of Examples 1-5 of the present invention are significantly higher than those of Comparative Examples 1 and 2, and have better stiffness performance. The stiff PBST and polylactic acid composite fiber provided by the present invention has better stiffness; compared with pure polylactic acid fiber, the stiff PBST and polylactic acid composite fiber provided by the present invention can be better suitable for disposable surgical clothing, can be completely biodegradable, and will not generate garbage after being discarded, and will not have any impact on the environment.
[0118] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0119] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a stiff PBST and polylactic acid composite fiber, wherein the stiff PBST and polylactic acid composite fiber comprises PBST fiber and polylactic acid fiber. After the composite fiber is formed, the PBST fiber is the skin layer of the composite fiber, and the polylactic acid fiber is the core layer of the composite fiber. The stiff PBST and polylactic acid composite fiber is obtained by composite spinning of PBST slices and polylactic acid slices, characterized in that: The preparation method of the stiff PBST and polylactic acid composite fiber comprises the following steps: Respectively obtaining the PBST slice and the polylactic acid slice; The stiff PBST slice and the polylactic acid slice are composite-spun so that the stiff PBST fiber is in the cortex of the composite fiber, and the polylactic acid fiber forms the core layer of the composite fiber, thereby obtaining the stiff PBST and polylactic acid composite fiber; the method for obtaining the stiff PBST slice comprises the following steps: After mixing terephthalic acid, succinic acid, butanediol and a catalyst, the mixture is added into a polymerization reactor, and the first esterification reaction is carried out at 160°C-180°C. When the esterification rate reaches 49.2%-49.9%, the first esterification reaction is completed; wherein the molar ratio of terephthalic acid, succinic acid and butanediol is in the range of 1.00: (1.30-1.34): (2.7-2.90), and the amount of the catalyst added is 0.02%-0.03% of the molar amount of the sum of the succinic acid and terephthalic acid; The temperature is raised to 205°C-215°C, and the second esterification reaction is completed when the esterification rate reaches 98.8%-99.8%; The temperature is raised to 240°C, a matting agent is added from the feeding port of the polymerization reactor, and the mixture is stirred for 15-20 minutes, and a pre-polycondensation reaction is performed for 20 minutes to 40 minutes. The amount of the matting agent added is 0.5% to 1.5% of the sum of the weight of terephthalic acid and succinic acid in terms of weight percentage; Vacuuming, heating to 250° C.-260° C., carrying out final polycondensation reaction, discharging and drying in sequence when the intrinsic viscosity is 0.75 dL / g-0.77 dL / g, and pelletizing to obtain the PBST slices, wherein the operating environment of the drying step is: the temperature range is 100° C.-105° C., and the drying duration range is 18h-24h; The stiff PBST and polylactic acid composite fiber is a completely biodegradable material with stiffness, an initial modulus value range of 48 cN / dtex-55 cN / dtex, and a 90-day degradation rate value range of 86%-90%.
2. The method for preparing the stiff PBST and polylactic acid composite fiber according to claim 1, characterized in that: The ratio of the cross-sectional area of the core layer to the cross-sectional area of the skin layer is in the range of (20-50): (50-80).
3. The method for preparing the stiff PBST and polylactic acid composite fiber according to claim 1, characterized in that: Observing from the cross section of the composite fiber, the core layer and the skin layer are in a concentric structure.
4. The method for preparing the stiff PBST and polylactic acid composite fiber according to claim 1, characterized in that: The tensile strength of the composite fiber is in the range of 3.5CN / dtex-4.5CN / dtex, and the elongation at break of the composite fiber is in the range of 25%-35%.
5. The method for preparing the stiff PBST and polylactic acid composite fiber according to claim 1, characterized in that: During the steps of evacuating the vacuum, heating to 250° C.-260° C., performing a final polycondensation reaction, and discharging and drying the material in sequence when the intrinsic viscosity is 0.75 dL / g-0.77 dL / g, and pelletizing to obtain the PBST slices, the method for determining the intrinsic viscosity comprises the following steps: Phenol and tetrachloroethane in a mass ratio of 1:1 are prepared as a solvent; Adding the PBST into the solvent to prepare a solution with a content of 0.1 g / dL; The intrinsic viscosity is obtained by measuring the intrinsic viscosity of the solution at 25°C using an Ubbelohde viscometer.
6. The method for preparing the stiff PBST and polylactic acid composite fiber according to claim 1, characterized in that: In the step, terephthalic acid, succinic acid, butanediol and a catalyst are mixed and added into a polymerization reactor, and a first esterification reaction is carried out at 160° C.-180° C. When the esterification rate reaches 49.2%-49.9%, the first esterification reaction is ended, and the catalyst is tetraisopropyl titanate.
7. The method for preparing the stiff PBST and polylactic acid composite fiber according to claim 1, characterized in that: The method for obtaining the polylactic acid slice comprises the following steps: Put polylactic acid into a mixer, add a matting agent, the amount of the matting agent added is 0.5%-1.5% of the mass of the polylactic acid, stir for 3min-5min to obtain a mixed material; The mixed material is placed in the main feeding port of a twin-screw extruder with a length-to-diameter ratio of (42:1)-(60:1), melt-extruded and granulated, and the extruded material is cooled, air-dried, pelletized and dried in sequence to obtain the polylactic acid slices; wherein the drying is vacuum drying, the drying temperature ranges from 105°C to 115°C, and the drying duration ranges from 24h to 36h.
8. The method for preparing the stiff PBST and polylactic acid composite fiber according to claim 7, characterized in that: The mixed material is placed at the main feeding port of a twin-screw extruder with a length-to-diameter ratio of (42:1)-(60:1), melt-extruded and granulated, and the extruded material is cooled, air-dried, pelletized and dried in sequence to obtain the polylactic acid slices. The temperature setting range of the twin-screw extruder is 165°C-210°C, the screw speed is 350rpm-400rpm, and the temperatures of each zone of the twin-screw extruder are: zone 1 temperature: 165°C-180°C, zone 2 temperature: 180°C-190°C, zone 3 temperature: 190°C-200°C, zone 4 temperature: 200°C-210°C, zone 5 temperature: 200°C-210°C, zone 6 temperature: 195°C-200°C, and zone 7 temperature: 190°C-195°C.
9. The method for preparing the stiff PBST and polylactic acid composite fiber according to claim 1 or 7, characterized in that: The matting agent is titanium dioxide, the purity range is 99.0%-99.9%, the type is rutile, the particle size is 50nm-100nm, the particles are white, and the weight average molecular weight is 70000-80000.
10. The method for preparing the stiff PBST and polylactic acid composite fiber according to claim 1, characterized in that: The process of composite spinning of the PBST slice and the polylactic acid slice is achieved by a one-step spinning-stretching method, and the stretching multiple is in the range of 4 to 6 times; The process conditions for composite spinning of the polylactic acid slice core layer and the PBST slice skin layer include: For the cortex: The temperature range of the components is 170℃-190℃. The screw pressure ranges from 10MPa to 12MPa; For the core layer: The temperature range of the components is 200℃-220℃. The screw pressure range is 8.0MPa-10.0MPa. The spinning speed ranges from 1200m / min to 1500m / min; The cooling method is air cooling, the blowing method adopts side blowing, and the blowing rate ranges from 3m / min to 5m / min.
11. Use of the stiff PBST and polylactic acid composite fiber prepared by the preparation method of the stiff PBST and polylactic acid composite fiber according to any one of claims 1 to 10 in disposable surgical clothing.
12. A surgical garment, characterized in that: The surgical garment is made of the stiff PBST and polylactic acid composite fiber prepared by the preparation method of the stiff PBST and polylactic acid composite fiber described in any one of claims 1-10.
